Development and Performance Evaluation of an Injection Moulding Machine for Recycled Polymer Composite Production - ADEODU, Adefemi O.; ADEDOKUN, Banjo C.; ADEGBITE, Amos A. (FUDMA Journal of Engineering and Technology, 2026)
The increasing demand for cost-effective polymer composite products with improved dimensional stability, mechanical properties, and surface quality has necessitated the optimization of injection moulding process parameters. However, inadequate control of injection pressure and injection time often results in poor mould cavity pressure distribution, leading to defects and inferior mechanical performance. This study investigated the effects of injection pressure and injection time on the mould cavity pressure of low-density polyethylene (LDPE) reinforced with aluminium powder and carbon black powders processed at 250°C and 200°C, respectively. Specifically, the study aimed to evaluate the influence of injection pressure and injection time on cavity pressure and establish their implications for product quality. An experimental research design was adopted using a locally fabricated injection moulding machine with a maximum injection pressure of 2,500 bar, a cylinder diameter of 22 mm, and a product capacity of 200 g. LDPE/aluminium and LDPE/carbon black composites were moulded under varying injection pressures and injection times, and cavity pressures were measured and analysed. The results showed a direct relationship between injection pressure and mould cavity pressure. For LDPE/aluminium, cavity pressure increased from 22 MPa to 42 MPa as injection pressure increased from 39 MPa to 70 MPa, while LDPE/carbon black recorded an increase from 20 MPa to 37 MPa under similar conditions. Conversely, increasing injection time reduced cavity pressure from 47 MPa to 30 MPa for LDPE/aluminium and from 39 MPa to 30 MPa for LDPE/carbon black. The study concludes that higher injection pressures and shorter injection times produce superior mould cavity pressures, resulting in improved dimensional stability, enhanced mechanical properties, and better surface appearance of moulded products. The study contributes empirical data for optimizing injection moulding parameters and provides a basis for improving the processing of reinforced LDPE composites.
Keywords: Composites, Cyclic manufacturing, defects, Injection moulding, Polymer.